Anti-SARS-CoV-2 antibody responses in convalescent plasma donors with varying clinical manifestation severity of COVID-19 - Grujić, Jasmina; Bujandrić, Nevenka; Budakov Obradović, Zorana; Savić, Nebojša; Dolinaj, Vladimir (Vojnosanitetski pregled, 2023)
Background/Aim. Plasma containing a high titer of anti-SARS-CoV-2 antibodies, donated from individuals who recovered from COVID-19, has the potential to be used as initial therapy for patients who have been infected (passive immunization). It is a challenge to find suitable donors. The aim of the study was to successively monitor antibody titer in donations and to investigate the correlation between antibody titer and the severity of the clinical manifestations. Methods. The retrospective study was conducted from May 1 to October 31, 2020, at the Blood Transfusion Institute of Vojvodina. Donors had to meet certain criteria for inclusion in the study: proven SARS-CoV-2 infection, detected SARS-CoV-2 antibodies in the serum/plasma, fulfillment of general criteria for performing plasmapheresis, and adequate laboratory findings. Results. During the study, 651 apheresis plasma units were collected and divided into two equal doses. Plasma was donated by 311 COVID-19 convalescents, including 208 (66.9%) men and 103 (33.1%) women. There were 15 (4.8%) plasma donors with asymptomatic infection, 235 (75. 6%) with a mild form of illness, 45 (14.5%) with a moderate form of illness, 16 (5.1%) with a severe form of illness, and none with a critical form of illness. Anti-SARS-CoV-2 IgG antibodies were present in the plasma of donors for more than 6 months after the disease. Plasma donors with a more severe clinical manifestation of COVID-19 had stable antibody levels for a longer period. However, the Pearson correlation of clinical severity and antibody titer did not confirm a statistically significant correlation between the variables. Conclusion. Anti-SARS-CoV-2 antibodies were present in the sample of recovered patients, plasma donors, for more than 6 months after the disease. Even though no statistically significant correlation was found between the anti-SARS-CoV-2 antibody titer and the clinical severity of COVID-19, in patients with a more severe clinical manifestations of the disease, stable antibody levels were maintained for a longer period.